On the shrinking projection method for nonexpansive mappings endowed with graphs - Kimura, Yasunori; Phothi, Supaluk; Tontan, Kittisak (Fixed point theory and algorithms for sciences and engineering, 2025)
Recently, the convergence of a shrinking projection method for a Hadamard space satisfying some properties endowed with a directed graph defined on a nonempty closed convex subset of this space has been studied by many authors. In this work, we define a new graph and consider a Hadamard space endowed with our modified graph, we present a theorem on the strong convergence of an iterative sequence generated by the shrinking projection method. In particular, we generalize a result in (Khatoon et al. in Proc. Est. Acad. Sci 71(3):275, 2022 ) to more general setting. The similar result is also deduces to a Hilbert space.